The Penguin historical atlas of the Third Reich - Overy, R. J. (New York : Penguin Books, 1996)
Charts the rise and fall of Hitler's Third Reich through a series of essays, photographs, and maps that reveal information about populations, sites of attacks, political support, and other topics, and includes a timeline and statistical appendix.
Includes bibliographical references and index.
Adult.
Adult
Keywords: National socialism -- Maps; Historical atlases; National socialism -- Maps; Germany -- History -- 1933-1945 -- Maps; Germany -- History -- 1933-1945 -- Maps